Keragaman Spesies Satwa Liar Berbasis Bidikan Kamera Jebak (Camera Trap) di Cagar Alam Pulau Sempu, Kab. Malang, Jawa Timur - Mohamad Sukron Makmum (LPPM Universitas Terbuka, 2023)
Concerns and vulnerability to the occurrence of damage to ecosystems in the Sempu Island Nature Reserve (CAPS), Malang Regency by human activities can have an impact on the survival of life and the decline of wildlife populations. The study aimed to calculate species richness and frequency of wildlife species encounters using camera traps in the CAPS area. The methodology uses the calculation of digital photographic recording evidence of camera traps. Wildlife caught on camera traps is calculated based on the number of photographs, the number of species, and the number of days the camera is active. The results showed a wealth of wildlife identified as many as 15 species, namely Muntiacus muntjak (Cervidae), Macaca fascicularis (Cercopithecidae), Paradoxurus hermaprodithus (Viverridae), Callosciurus notatus (Sciuridae), Tragulus javanicus (Tragulidae), Hystrix javanica (Hystricidae), Trachypithecus auratus (Cercopithecidae), Sus scrofa (Suidae), Prionodon linsang (Prionodontidae), Varanus nebulosus (Varanidae), Gallus gallus (Phasianidae), Chalcophaps indica (Columbidae), Spilornis cheela (Accipitridae), Hydrornis guajanus (Pittidae) and Varanus salvator (Varanidae). The results of calculating the frequency of wildlife encounters vary relatively from high to low values, but of the 15 species recorded the highest gains, Muntiacus muntjak (ER 11.17 photos / day) and Macaca fascicularis (ER 10 photos / day).